Surgical treatment of pneumatosis cystoides intestinalis with pneumoperitoneum secondary - Okuda, Yoshihiro; Mizuno, Shugo; Koide, Taihei; Suzaki, Makoto; Isaji, Shuji (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Okuda Y, Mizuno S, Koide T, Suzaki M, Isaji S. Surgical treatment of pneumatosis cystoides intestinalis with pneumoperitoneum secondary to sigmoid volvulus following one year of follow-up. Turk J Gastroenterol 2018; 29: 127-9.